Aspectos jurídicos dos fundos de investimentos sob a ótica da governança corporativa - Ferreira, Cláudio de Araújo (2012)
The aim of this work lays on working around the corporate governance history in Brazil and worldwide, besides its application to investment´s funds world. Catching a glimpse when it comes to mention the relationship between governance and capitalism, Corporations upcoming, distinct recessions by which the system had to pass through and how the evolution took place upon such scenario is exactly the path to be studied here; up to the concept of corporate governance nowadays, including taking into account the definition provided by the Instituto Brasileiro de Governança Corporativa. Comparing the existing domestic legislation is necessary in first place in order to comprehend which are the mandatory rules and among them, the ones issued by the Comissão de Valores Mobiliários and Banco Central do Brasil, such as it is also to understand the legal limitations on Brazil´s investment funds. By verifying the analysis of distinct types of funds of investments that are in place today, it will be clarified some important aspects such as administration side, management, investment policies and focusing limitations among other subjects. Choosing such subject is well justified due to the small bibliography about it existing nowadays, and also taking into account the upcoming creation and evolution of investment funds in the Brazilian market besides the shortage of decision making about it and the great relevance of such vehicles in getting the popular savings representing Brazil and their chance to grow as verified in countries where the capital markets, the ones the most developed as United Stated and England